Digital Transformation and Inclusive Growth in South Korea and Indonesia - chitra imelda; Alfitri; Andries Lionardo; Abdul Najib (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
This study examines the role of digital transformation policies in South Korea and Indonesia, focusing on the Digital New Deal and the Palapa Ring Project, respectively. These initiatives aim to improve digital access, reduce social inequality, and promote economic growth through technology. This study uses a descriptive qualitative method with a case study approach, utilizing secondary data from official reports and surveys. Findings show that the Digital New Deal in South Korea has accelerated the digitization of the public sector, created jobs, and improved access to services. On the other hand, the Palapa Ring Project in Indonesia has expanded internet connectivity in remote areas, but faces challenges in infrastructure quality and digital literacy. This study emphasizes the importance of collaboration between the public and private sectors and provides insights into how digital policies can promote inclusive growth and reduce inequality. The study concludes that although both initiatives show potential, addressing challenges in infrastructure and digital education remains crucial for sustainable transformation.